2018
DOI: 10.1111/ane.13030
|View full text |Cite
|
Sign up to set email alerts
|

Early-SEPs’ amplitude reduction is reliable for poor-outcome prediction after cardiac arrest?

Abstract: Not only the absence but also a bilateral amplitude reduction of cortical SEPs (<0.65 μV) is associated with ominous prognosis (death or non-recovery of consciousness) with a very high predictive value. However, we emphasize that great caution should be applied before adopting amplitude reduction as a criterion for the poor prognosis of CA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
4
19
1
Order By: Relevance
“…Our results confirm earlier findings on the relevance of SSEP amplitude for outcome prediction of comatose patients after cardiac arrest. However, these studies on SSEP amplitude reported higher cut off values for poor outcome prediction of approximately 0.6 µV (16,17). In these previous studies, SSEP was often recorded very early, during treatment with targeted temperature management and sedation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results confirm earlier findings on the relevance of SSEP amplitude for outcome prediction of comatose patients after cardiac arrest. However, these studies on SSEP amplitude reported higher cut off values for poor outcome prediction of approximately 0.6 µV (16,17). In these previous studies, SSEP was often recorded very early, during treatment with targeted temperature management and sedation.…”
Section: Discussionmentioning
confidence: 94%
“…However, only few studies addressed the role of SSEP amplitude. Two studies show that an early N20 amplitude <0.65 µV (16) or <0.62 µV (17) reliably predicts poor outcome, even when tested during treatment with sedative drugs or hypothermia. However, others stress that low or even absent SSEP responses can be found during treatment with hypothermia in patients with a good recovery (18).…”
Section: Introductionmentioning
confidence: 99%
“…SEP analysis was based on the evaluation of the presence, amplitude [3]or absence of the cortical responses (N20/P25 complex) on both hemispheres [4]. We identified six SEP patterns: NN, NP, PP, AN, AP and AA, in which N stands for normal (N20/P25 amplitude is normal), P stands for pathological (N20/P25 amplitude is < 1.2μV or the difference between the two sides is greater than 50%) and A stands for absent if no reproducible cortical components could be identified in the presence of a lemniscal potential [5,6].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…This study has limitations. N20 was dichotomized as present or absent, without amplitude threshold or frequency analysis 12 . Early EEG was rescored retrospectively, but blinded to outcome and using the same criteria than subsequent recordings.…”
Section: Resultsmentioning
confidence: 99%
“…N20 was dichotomized as present or absent, without amplitude threshold or frequency analysis. 12 Early EEG was rescored retrospectively, but blinded to outcome and using the same criteria than subsequent recordings. The absence of formal blinding to the respective results of SSEP and EEG might have led to overinterpretation of EEGs as "benign" in case of known present SSEPs, or consideration of "doubtful" SSEPs as present in patients with "benign EEG".…”
Section: Con Clus Ionmentioning
confidence: 99%